Pengaruh Meme Terhadap Identitas Pemuda Muslim Nusantara: Telaah Respons Konten Instagram - Rozaq, Muhammad Fathur (Analisis: Jurnal Studi Keislaman, 2019)
Now Instagram is a popular social media platform that is popular and influential, especially among youth. Instagram contains less than two minutes of video content, photos, and caricature images and a series of words, wisdom, humor, even satire, all of which are often called memes. whether the idea or idea carried by a particular account is accepted, appreciated, or otherwise gets resistance from its followers. To find out, this requires observing their actions in response to certain content on a particular account. This article will discuss how Muslim youth in the country respond to ideas spread on Instagram. by looking at how they like and comment on content. The study uses a descriptive analysis approach. Three things the authors capture from this phenomenon. First, the discourse most favored by Muslim youth is the issue of romance. Second, thinking power is less critical especially when dealing with dogmatic content. Third, their attitude tends to be quiet when treated with commodified content. And it can be concluded that love issues are most in demand than religious issues and other issues.